Capacity Building in Cooperative Organization: Ground for Change - A. Emejulu Gerard; Nwachukwu Oforbuike Francis; Okafor Ogochukwu Esther; Taiwo Olabisi Abdulahi (Archives of Current Research International, 2019)
The concept of capacity building in cooperative society exist in all aspect of cooperatives activities and it is the important strategy that enable cooperative society and its members to perform effectively well in line with their goal and cooperative principles. For any cooperative society to perform very well and be able to compete favorably, it must invest reasonable amount of money to develop the ability of its members, employees and the society itself.